Inovasi Pengolahan Limbah Kulit Pisang Raja Nangka menjadi Tepung Bernilai Ekonomi pada Sentra Getuk Pisang Desa Petok, Kediri - Lisanty, Nina; Sutiknjo, Tutut Dwi; Junaidi, Junaidi; Muharram, Muhammad; Nurhamidah, Siti (Kadiri University, 2025)
Petok Village, located in Mojo District, Kediri Regency, is known as a major center for getuk pisang (banana cake) production that has been sustained across generations. However, the production process generates large amounts of waste from raja nangka banana peels that remain unutilized. The banana peel waste generated from these home-based industries has the potential to pollute the environment if not properly managed and disposed of. Based on previous research on the formulation of banana peel flour as a functional food ingredient, this activity aimed to transfer knowledge and skills to getuk pisang producers, enabling them to process banana peel waste into value-added flour. The program was conducted using a participatory approach involving socialization sessions, direct demonstrations of banana peel flour production, and discussions on business opportunities derived from the process. The results showed an 85% increase in participants’ knowledge and skills, as measured by pre- and post-tests. In addition to producing quality banana peel flour, the activity also fostered awareness of circular economy concepts and local resource utilization. This community empowerment initiative presents opportunities for establishing a joint business group focused on banana peel flour processing, as well as collaboration with the village government for product development and sustainable marketing. Desa Petok di Kecamatan Mojo, Kabupaten Kediri, dikenal sebagai sentra penghasil getuk pisang yang telah bertahan lintas generasi. Namun, produksi getuk pisang menghasilkan limbah kulit pisang raja nangka dalam jumlah besar yang belum termanfaatkan secara optimal. Limbah kulit pisang yang dihasilkan dari industri rumahan getuk pisang berpotensi mencemari lingkungan jika tidak dikelola dengan baik. Berdasarkan hasil penelitian sebelumnya tentang formulasi tepung kulit pisang sebagai bahan pangan fungsional, kegiatan ini bertujuan mentransfer pengetahuan dan keterampilan kepada pelaku usaha getuk pisang agar mampu mengolah limbah kulit pisang menjadi tepung bernilai ekonomi. Metode pelaksanaan dilakukan melalui pendekatan partisipatif yang meliputi sosialisasi, demonstrasi pembuatan tepung kulit pisang, serta diskusi peluang usaha turunan. Hasil kegiatan menunjukkan peningkatan pengetahuan dan keterampilan peserta sebesar 85% berdasarkan pre-test dan post-test. Selain menghasilkan produk tepung kulit pisang berkualitas, kegiatan ini juga menumbuhkan kesadaran tentang konsep ekonomi sirkular dan potensi diversifikasi produk berbasis bahan lokal. Kegiatan ini berimplikasi pada peluang pembentukan kelompok usaha bersama pengolahan tepung kulit pisang serta kerja sama dengan pemerintah desa untuk pengembangan produk olahan dan pemasaran berkelanjutan.